ANALISIS POTENSI DAERAH PASURUAN DALAM MENINGKATKAN PEREKONOMIAN REGIONAL DENGAN METODE LQ & SHIFTSHARE - Yunita Sari, Frisca (Pusat Riset dan Inovasi Nasional, 2022)
The Pasuruan area is one of the districts in East Java Province. This area has potential in its natural resources which we know is close to the mountains, beaches, and also the city center. The author analyzes what sectors have the potential in this area for the economy as a reference for further directed development and aims to prosper the community. The research method used is descriptive quantitative method with two calculations, namely the Location Quetiont method and the Shiftshare method with reference data for the GRDP of the business field according to 2010 constant prices in 2014-2018. The industrial sector as well as wholesale trade, restaurants, hotels and financial services has a positive value which means it has great potential as a contributor to GRDP in East Java and is also a form of empowering the community to achieve a prosperous society. With the hope that further development can be more focused and on target.